(untitled) (Research, Society and Development, 2023)
The implications caused by the actions of fire resulted in an impoverished soil and forest species, rivers and streams were negatively affected. It was the target of motivation and awakening of the farmers for the option of new production systems, hence the perspective of the implantation of the Agroforestry Systems - AFS’s in order to solve this crisis that compromised the production, consumption and commercialization of the surpluses. The general objective of this study was to verify whether the implementation of SAFs brought social, economic and environmental benefits, environmental services, to family farmers in the municipality of Irituia. The methodological path is restricted to a systematic review, based on consultation with the collection of educational institutions, articles published in magazines, collections with a view to obtaining information focusing on the crisis and the reestablishment of commercialization and agricultural production, based on the implementation of Agroforestry Systems – AFS’s in the Municipality of Irituia, State of Pará. The implemented systems have become promising due to the adoption of sustainable production practices and the research carried out reinforces this conclusion.